Microfluidic detachment assay to probe the adhesion strength of diatoms - Alles, Maria; Rosenhahn, Axel (Biofouling, 2015)
Fouling release (FR) coatings are increasingly applied as an environmentally benign alternative for controlling marine biofouling. As the technology relies on removing fouling by water currents created by the motion of ships, weakening of adhesion of adherent organisms is the key design goal for improved coatings. In this paper, a microfluidic shear force assay is used to quantify how easily diatoms can be removed from surfaces. The experimental setup and the optimization of the experimental parameters to study the adhesion of the diatom Navicula perminuta are described. As examples of how varying the physico-chemical surface properties affects the ability of diatoms to bind to surfaces, a range of hydrophilic and hydrophobic self-assembled monolayers was compared. While the number of cells that attached (adhered) was barely affected by the coatings, the critical shear stress required for their removal from the surface varied significantly.
Gesehen am 22.07.2020